Growth and Short Term Egg Production of Two Exotic (Layer Type) and the Local Chickens Compared with Their F1 Inbred Progenies - Udeh , I.; Omeje, S.I. (International Journal of Poultry Science, 2011)
The objective of this study was to compare the growth and short term egg production of two exotic and the local chicken with those of their F1 inbred progenies in order to determine the effect of one generation of full sib mating on these traits. The two exotic chickens were H and N Brown Nick (strain 1) and Black Olympia (strain 2) while the local chicken was strain 3. The experimental birds were raised in deep litter pens from day old to 40 weeks of age. The coefficient of inbreeding of the three strains were as follows: strain 1 (10.80%), strain 2 (9.00%) and strain 3 (11.80%). Body weight, weight gain, age at first egg, age at peak egg production, egg weight, hen day rate and feed per dozen eggs were significantly (p